2020
DOI: 10.3389/fvets.2020.00588
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Protects Against Aerococcus viridans Infection in a Murine Mastitis Model

Abstract: Bovine mastitis, an inflammatory disease that occurs frequently in early lactation or the dry period, is primarily caused by bacterial infections. There is growing evidence that Aerococcus viridans (A. viridans) is becoming an important cause of bovine mastitis. The treatment of bovine mastitis is primarily based on antibiotics, which not only leads to a large economic burden but also the development of antibiotic resistance. On the other hand, bacteriophages present a promising alternative treatment strategy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…Compared with the control group of crucian carp, the inflammation and pathological changes were significantly alleviated in the gut and spleen tissues from crucian carp that were treated with phage. Furthermore, compared with the control group, vB_CbrM_HP1 administration resulted in a decrease in cytokine (TNF-α, IFN-γ, IL-1β) levels which was the same phenomenon as seen in the phage PIZ SAE-01E2 and the phage AVP in the treatment of infection with S. abortus equi and A. viridans, respectively (33,68). These results showed that phage vB_CbrM_HP1 can effectively alleviate lesions in vivo.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Compared with the control group of crucian carp, the inflammation and pathological changes were significantly alleviated in the gut and spleen tissues from crucian carp that were treated with phage. Furthermore, compared with the control group, vB_CbrM_HP1 administration resulted in a decrease in cytokine (TNF-α, IFN-γ, IL-1β) levels which was the same phenomenon as seen in the phage PIZ SAE-01E2 and the phage AVP in the treatment of infection with S. abortus equi and A. viridans, respectively (33,68). These results showed that phage vB_CbrM_HP1 can effectively alleviate lesions in vivo.…”
Section: Discussionsupporting
confidence: 56%
“…The pH and temperature stability tests were performed on the basis of a previously described method (33). vB_CbrM_HP1 with the same titer (10 10 PFU/ml) was incubated in SM buffer (pH 2-11) at 37 • C for 2 h. For the temperature stability test, vB_CbrM_HP1 with the same titer (10 10 PFU/ml) was incubated at 4 • C, 25 • C, 37 • C, 50 • C, 60 • C, 70 • C and 80 • C, and samples were taken every 20 mins to determine the phage titer.…”
Section: Biological Characteristics Of Vb_cbrm_hp1mentioning
confidence: 99%
“…Several researchers have reported that the 4th pair of mouse mammary gland have been used as an infection model to test the therapeutic effects of gut microbiota, probiotics and phage ( Wang et al, 2017 ; Hu et al, 2020 ; Ngassam-Tchamba et al, 2020 ). Therefore, a model of mastitis induced by S. dysgalactiae in mice was established in this work, which showed the typical symptoms of mastitis at the 4th pair of mouse mammary tissue as previously reported ( Xi et al, 2020 ), the swelling, congestion and hemorrhage mammary tissue and the increased inflammatory cytokines. Compared with the vancomycin treatment group, NZ2114 displayed significant decrease of bacteria and immunomodulatory effects against S. dysgalactiae -induced mastitis, and the effect of NZ2114 was superior to that of vancomycin.…”
Section: Discussionmentioning
confidence: 60%
“…Several phages have been identified for these purposes, but a greater proportion of work has been conducted on S. aureus being the common aetiological agent causing this infection. This approach has also been described for bacterial species such as A. viridans [ 68 ], E. coli [ 60 ] and K. oxytoca [ 9 ].…”
Section: The Case For Phage Therapy To Control Bovine Mastitismentioning
confidence: 99%